Interiorized urbanization: new conformations in the Brazilian Northeast territory - Bezerra, Josué Alencar (Sociedade & Natureza, 2020)
The issue of this study points to a concrete object, whose reference is the configuration of an internalized urban network in the Brazilian Northeast. To understand this, we studied the formation of the network of cities in the region, considering the urbanization of the territory, until the last decades. We used the theoretical contribution in bibliographic readings of works that deal with the theme. We analyzed the transformations in the territory accompanied by the restructuring of the economy, the growth of the number and size of cities and the representative increase of the urban roles in the territorial division of labor. We identified in Northeast Brazil an internalized urban network organized and dynamic, with the diffusion of new urban centralities far from the great centers of the region.